52nd IEEE Conference on Decision and Control 2013
DOI: 10.1109/cdc.2013.6760759
|View full text |Cite
|
Sign up to set email alerts
|

Robustness analysis of a Moving Horizon Estimator for space debris tracking during atmospheric reentry

Abstract: Trajectory estimation during atmospheric re entry of ballistic objects such as space debris is a very complex problem due to high variations of their ballistic coefficients. In general, the characteristics of the tracked object are not accurately known and an assumption on the dynamics of the ballistic coefficient has to be made in the estimation model. The designed estimator must hence prove to be robust enough to such model uncertainties, and to bad initialization if no good prior information on the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The main advantages of the MHE are that it allows to handle nonlinear systems without linearisation and to incorporate constraints directly during the optimization. The MHE has also been shown to be more robust against poor initialization than the Extended Kalman Filter (EKF) [5], the Unscented Kalman Filter (UKF) and the particle filter [9]. The convergence of the estimation errors of the MHE has been demonstrated in [2] provided that a quadratic arrival cost is adopted and its weight matrix is adequately chosen.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of the MHE are that it allows to handle nonlinear systems without linearisation and to incorporate constraints directly during the optimization. The MHE has also been shown to be more robust against poor initialization than the Extended Kalman Filter (EKF) [5], the Unscented Kalman Filter (UKF) and the particle filter [9]. The convergence of the estimation errors of the MHE has been demonstrated in [2] provided that a quadratic arrival cost is adopted and its weight matrix is adequately chosen.…”
Section: Introductionmentioning
confidence: 99%
“…To derive an estimation model for the estimators, let us assume that β is constant over a sampling period T s . The following state equation is obtained [11]:…”
Section: B Estimation Modelmentioning
confidence: 99%
“…the Earth gravity constant, and w k is a modeled as a discretetime zero-mean truncated gaussian white noise of covariance matrix Q. This matrix can be parameterized as Q = Q(T s ).q z where the matrix Q(T s ) can be found in [11] and the scalar q z > 0 should account for both discretization error and model errors, from the fact that β is not constant over a sampling period.…”
Section: B Estimation Modelmentioning
confidence: 99%
“…The estimation errors, nondivergence percentage and computation time of the MHE-PE will be compared to those of the EKF, the UKF and the RPF through Monte Carlo simulations. Compared to previous work [17], a new estimation model using the derivative of the acceleration is proposed in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…An assumption on its variation has to be made in the estimation model which results in model errors. In the previous work by the authors [17], we showed that, for a simplified 1D space debris tracking during the re-entry, classical estimators such as the Extended Kalman estimator (EKF), the Unscented Kalman estimator (UKF) and the Regularized Particle estimator (RPF) are outperformed by the Moving Horizon Estimator (MHE) in terms of robustness against poor initialization and accuracy. However, the MHE requires very large computation time and its implementation in 3D cases is limited.…”
Section: Introductionmentioning
confidence: 98%